An Assessment on the Relationship Between Informal Economy and Educational Level in Turkey - Ela, Mehmet (International Journal of Economics and Financial Issues, 2013)
The informal economy is an obscure concept but it contains several economic transactions. It is a very difficult task to measure its size and dimensions, however economists have developed reliable methods to predict the size and impact of informal economy in a given country or economic region. Studies in Turkey and abroad indicate that informal economy in this country is considerably large and sprawling. Existence of informal economy is a significant problem in any country since it negatively affects the national economic system. So far, policies deployed to deal with the negative outcomes of informal economy in Turkey mainly focused on tax policies and wages. On the other hand, increased educational attainment and provision of contemporary educational programs should be considered as better means to reduce the size and negative impact of informal economy. However, before using education to solve problems related to informal economy, the educational system needs to be restructured along with other restructuring efforts in economy, politics and legal systems. Increased educational attainment should also contribute to resolution of such social problems as economic growth and unfair income distribution in the country. Keywords: Informal economy; education; informal employment JEL Classifications: E24; E26; H52